Effect of Deep Stretching Minimizing the Incident of Low Back Pain on Rice Farmers in Pudak Village Muaro Jambi District Year 2024 - Amilda Putry Apryanti; Puspita Sari; Budi Aswin (Formosa Journal of Multidisciplinary Research, 2024)
Low back pain (LBP) is a musculoskeletal disease that can be disturbing and the main cause is physical disorders. World Health Organization estimates that industrialized countries experience low back pain disorders with a prevalence of 5% per year and Indonesia with a prevalence rate of 49%. In Jambi, the prevalence of disease among farmers has the highest prevalence of 12.79%. This research aims to determine the effect of stretching in minimizing LBP in rice farmers in Pudak Village. This research uses quantitative research methods with a quasi-experimental type. The research sample consisted of 20 farmers who were divided into 2 groups, the treatment and the control group. In the treatment group experienced a decrease in the average level of pain after being given stretching. The results show that there is an effect of stretching with LBP.